Striking Evidence: The Impact of Railway Strikes on Competition from Intercity Bus Services in Germany - Matthias Beestermöller; Levke Jessen-Thiesen; Alexander Sandkamp; Alexander-Nikolai Sandkamp (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper investigates the impact of the largest rail strikes in German history on intercity buses – a then newly liberalised market. Using unique booking data of bus services, we exploit variation in rail service cancellations across routes to show that the disruption in rail transport increases bus ticket sales. Crucially, the effect persists beyond the strike, indicating that travellers do not return to their originally preferred mode of transport. It is particularly pronounced for passengers travelling on weekends. The findings suggest that customers were previously under-experimenting. Beyond transportation, our results highlight the importance of service reliability, as temporary disruptions can cause customers to permanently switch to competitors.
Keywords: C81; D83; L92; R41; 330; experimentation; inter-modal substitution; learning; optimisation; strike; switching costs; transport